An in-vitro study on the accuracy of conventional film optical densitometry and densitometry in radiovisiography system - Bashizadeh H; Talaeepour A; Dabbaghi (Tehran University of Medical Sciences, 2002)
Nowadays, bone mass estimation, through imaging methods, is widely used in metabolic"ndiseases diagnosis and treatment. One of these methods is called "optical densitometry" which estimates bone density by measuring the intensity of the transmitted light on different parts of a radiographic image. Digital radiography systems act similarly by determining grey levels of the image. The aim of this study is comparing two different methods of optical densitometry and a digital system densitometry known as radiovisiography. 45 samples, containing urografin with three different concentrations, were imaged, by both radiovisiogrphy (RVG) and conventional film systems. To determine the densitometry of films and radiovisiography images, optical densitometry and bone densitometry option of the RVG software, were applied respectively. Data were analyzed and compared for their reliability (repeatability) and correlations with concentration. In RVG densitometry system, the correlation with concentration is moderate (r=0.42) and intra samples and intra group reliability are 97.68% and 88.19%. Moreover, in conventional optical film densitometry, correlation with concentration (r=0.987) is high, intra samples and intra group reliability is high, intra samples and intra group reliability are 99.97% and 99.84%, respectively. According to the results, it is suggested that conventional film optical densitometry is more precise and reliable than RVG densitometry.